Ethnohistory and Archaeology
XVI, 238 p.
Keywords: Incorporating both archaeological and ethnohistorical evidence, this volume reexamines the role played by native peoples in structuring interaction with Europeans. The more complete historical picture presented will be of interest to scholars and students of archaeology, anthropology, and history.